Mobile marketing: an approach on advertising by SMS - Silva, Alandey Severo Leite da; Rabelo Neto, Alexandre; Luna, Roger Augusto; Cavalcante, Gustavo Teotonio de Oliveira; Moura, Alexandre Ramos de (Revista de Administração da UFSM, 2019)
The increasing use of mobile devices is becoming most important to the execution of marketing actions through mobile systems. According to Ibope (2013), eMarketer estimates that global investment in mobile advertising will triple in 2015, which shows the growing importance of the mobile environment in the business world. This article aims to analyze the factors that influence the acceptance of advertising by SMS from students in public universities of Campina Grande/PB, using Marisavo et al. (2007)’s model. Based on said model, a questionnaire was developed, proposed and answered by 200 students of two public universities. The results showed that the factor that most influences positively the acceptance of advertising by SMS is the perception of control that consumers have about receiving this type of advertising.